2022
DOI: 10.1007/s10869-022-09805-3
|View full text |Cite
|
Sign up to set email alerts
|

When Does Safety Climate Help? A Multilevel Study of COVID-19 Risky Decision Making and Safety Performance in the Context of Business Reopening

Abstract: Businesses are gradually reopening as lockdown measures for the coronavirus disease 2019 (COVID-19) pandemic are being relieved in many places across the globe. It is challenging but imperative for businesses to manage the risk of infection in the workplace and reopen safely. Drawing on risky decision-making theory and the job demands-resource model of workplace safety, we examined the influences of employees’ COVID-19 risk perception on their safety performance at work. On the one hand, COVID-19 risk percepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Emerging literature on WSPs during this pandemic has already provided important insights into the influence of various pandemic related stressors on safety compliance ( Probst, Lee, & Bazzoli, 2020 ) and wellbeing of employees ( Lin, Shao, Li, Guo, & Zhan, 2021 ); as well as the role of the organization ( He et al, 2021 , Kim et al, 2021 ) and leaders ( Yuan et al, 2020 , Zhang et al, 2020 ) in promoting employee engagement and conformance to safety procedures. For instance, a recent study conducted in China revealed that FLE perceptions of risks from COVID-19 translated into anxiety, which further led to lower levels of safety related behaviors ( Wang, He, Sheng, & Yao, 2022 ). Further, the literal life-and-death implications of what organizations can do to ensure the safety of FLEs (e.g., option to work at home, use of personal protective equipment) have been discussed in both the popular press and academic journals, all of which highlight the physical and psychological impact of WSPs on employee wellbeing ( Carnevale and Hatak, 2020 , Finsterwalder and Kuppelwieser, 2020 , Voorhees et al, 2020 ).…”
mentioning
confidence: 99%
“…Emerging literature on WSPs during this pandemic has already provided important insights into the influence of various pandemic related stressors on safety compliance ( Probst, Lee, & Bazzoli, 2020 ) and wellbeing of employees ( Lin, Shao, Li, Guo, & Zhan, 2021 ); as well as the role of the organization ( He et al, 2021 , Kim et al, 2021 ) and leaders ( Yuan et al, 2020 , Zhang et al, 2020 ) in promoting employee engagement and conformance to safety procedures. For instance, a recent study conducted in China revealed that FLE perceptions of risks from COVID-19 translated into anxiety, which further led to lower levels of safety related behaviors ( Wang, He, Sheng, & Yao, 2022 ). Further, the literal life-and-death implications of what organizations can do to ensure the safety of FLEs (e.g., option to work at home, use of personal protective equipment) have been discussed in both the popular press and academic journals, all of which highlight the physical and psychological impact of WSPs on employee wellbeing ( Carnevale and Hatak, 2020 , Finsterwalder and Kuppelwieser, 2020 , Voorhees et al, 2020 ).…”
mentioning
confidence: 99%
“…In the context of a virtual workplace where supervisors employ abusive tactics, the employees may find themselves lacking the necessary resources to cope with the stressful conditions (Zhang et al, 2019). Furthermore, abusive supervision during forced teleworking heightens employees' ambiguity and uncertainty surrounding COVID-19 (Wang et al, 2022), which in turn triggers anxiety and insecurity, hindering employees' ability to remain present in the moment (Alo et al, 2023;Zheng et al, 2022). Consequently, employees experience resource depletion due to abusive supervision in the context of COVID-19.…”
Section: Abusive Supervision and State Mindfulnessmentioning
confidence: 99%
“…Consequently, work barriers have emerged, leaving managers uncertain about employees' productivity and engagement (Heidt et al ., 2022; Lewis et al ., 2023; McPhail et al ., 2023). This new reality has triggered destructive behavior among leaders (Wang et al ., 2022; Simard and Parent-Lamarche, 2021), leading to the development of abusive supervision. Abusive supervision refers to “subordinates' perception of the extent to which supervisors engage in the sustained display of hostile verbal and nonverbal behaviors, excluding physical contact” (Tepper, 2000, p. 178).…”
Section: Introductionmentioning
confidence: 99%
“…First, abusive supervision may trap subordinates in a negative state and damage their well-being, as illustrated by increased burnout [ 28 ]. Simultaneously, in times of uncertainty and economic turndown, some employees may also worry about external threats, such as the negative impact of industry turndown on organizations, the loss of revenues or sales, and the possibility of losing their jobs [ 42 ]. In the time of COVID-19, those worries become realistic as some companies have closed, and some industries continue layoffs [ 43 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%